2019
DOI: 10.1016/j.tranon.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

MYC-Induced miR-203b-3p and miR-203a-3p Control Bcl-xL Expression and Paclitaxel Sensitivity in Tumor Cells

Abstract: Taxanes are chemotherapeutic agents used in the treatment of solid tumors, particularly of breast, ovarian, and lung origin. However, patients show divergent therapy responses, and the molecular determinants of taxane sensitivity have remained elusive. Especially the signaling pathways that promote death of the taxane-treated cells are poorly characterized. Here we describe a novel part of a signaling route in which c-Myc enhances paclitaxel sensitivity through upregulation of miR-203b-3p and miR-203a-3p; two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 43 publications
(80 reference statements)
5
19
0
Order By: Relevance
“…Multidrug resistance (MDR) is generally considered to be a major factor in the failure of many forms of chemotherapy. Recently, growing body of reports have suggested that several miRNAs are closely associated with MDR and they can modulate drug sensitivity in TNBC [78][79][80][81][82][83][84]. Tan et al [79] found that miR-638 can affect DNA repair and sensitivity to UV and cisplatin.…”
Section: Regulate Radiosensitivity and Chemosensitivitymentioning
confidence: 99%
“…Multidrug resistance (MDR) is generally considered to be a major factor in the failure of many forms of chemotherapy. Recently, growing body of reports have suggested that several miRNAs are closely associated with MDR and they can modulate drug sensitivity in TNBC [78][79][80][81][82][83][84]. Tan et al [79] found that miR-638 can affect DNA repair and sensitivity to UV and cisplatin.…”
Section: Regulate Radiosensitivity and Chemosensitivitymentioning
confidence: 99%
“…Although Bcl-xL serves as a promoter of various types of cancers due to its antiapoptotic effects, requiring targeted knockdown therapy [17][18][19], it has also been found to inhibit inflammation in some diseases due to its antiapoptotic effects [20,21]. The purpose of this study was to investigate the expression of Bcl-xL in cartilage damage caused by osteoarthritis and determine its effect on chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from binding competition of miRNA towards hub genes, the combined ways of TFs with miR-204-5p and genes were still in doubt due to lack of database prediction, experimental proof and literature confirmation directly repressing E2F1, a MYC-collaborating molecule [52]. In breast tumor, MYC expression correlates positively with miR-203b-3p and miR-203a-3p but negatively with BCL2L1 expression, resulting in formation of a TF-FFL [113]. MIR7-3HG restrains MYC dephosphorylation by downregulation of AMBRA1 to form a positive feedback loop for its own expression and further contributing significantly to autophagic control [114].…”
Section: Discussionmentioning
confidence: 99%